Industrial training report Perpustakaan Tengku Anis / Nur Shamilah Mat Seman - Mat Seman, Nur Shamilah (School of Information Science, College of Computing, Informatics and Media, 2023)
This industrial training report consists of four chapters that includes the introduction, organization information, industrial training activities and conclusion. I have made application to do industrial training at an academic library which known as Perpustakaan Tengku Anis, UiTM Cawangan Kelantan. Industrial training started from 1st September 2022 until 31st January 2023. Within the five months of practical training at the library, I was given tasks that related to library field. On the first day I reported myself at the library, Madam Norfitriah binti Mat Seman that positioned as the Librarian and my supervisor in PTA give the industrial training schedule by. In addition, I gained much knowledge, experiences, and new skills especially when I was training under different department at PTA such as Corporate Communication Unit, Printed Resource Unit, Electronic Source Unit, Customer Service Unit and others. During industrial training I was able to experience the work environment in library field.